IMPROVING TUBERCULOSIS RESPONSE STRATEGIES BY INVOLVING THE PRIVATE SECTOR IN THE PUBLIC-PRIVATE MIX SCHEME: A SYSTEMATIC REVIEW - Novie Irawaty L. Manurung; Ede S. Darmawan; Putri Ardhani (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
Private sector involvement in national tuberculosis (TB) programs positively impacts prevention and service, but challenges remain. The World Health Organization (WHO) provides a framework to enhance public-private engagement. Our aims were to explore evidence and measure success in TB control programs. We conduct systematic literature reviews using PubMed, Embase, and ProQuest databases to find reports published in English with no time limit. PRISMA was used to filter titles and abstracts for inclusion. A search of 176 studies found that 14 fit the inclusion criteria, with 92.8% collaborating on multiple interventions for TB outcomes. Private sector support, health worker assistance, and innovative projects, such as medical associations and religious organizations, improved TB program achievement. In conclusion, the government has implemented four intervention strategies from the WHO framework to increase private sector engagement in each region. These strategies must be implemented in the local context, with a focus on medium and long-term implementation to ensure sustainable results.